The Effect of Factors of E-marketing on Purchase Decision in MSME`s snack product: A case study in PT. Saikho Indo Kreatif - Wiadi, Iyus; Mudrika, Siti; Suharjo, Diyono; Ahmad-Azmy; Deni, Deni (Zielona Góra: Faculty of Economics and Management Press)
Due to the multiple advantages that it offers to both sellers and consumers, the digitalization of services is a process that is gaining popularity on a global scale. The aim of this research was to explore the impact of e-marketing elements related to SME products on sustainable customer behavior in the context of purchasing decisions.
Keywords: e-marketing; purchase decision; small-medium entreprise; consumer behavior